Effect of weed management on the population of macadamia nutborer Ecdytolopha torticornis Meyrick (LEP: Tortricidae). - Blanco-Metzler, Helga; Villalobos, Rodolfo; Wat, Allan D.; Cosens, Derek (Agronomía Mesoamericana, 2016)
The effect of three weed management systems -macadamia husk as a mulch, bare ground and weeds growing freely - on the population ofthe nutborer, Ecdytolopha torticornis, were studied from June to September 1992 at Oriente Farm, Turrialba, Costa Rica. The smallest number of the nutborer's eggs was recorded on the bare ground treatment, followed by the unweeded treatment and the husk treatment. Although the macadamia husk as a mulch has been used to sol ve the problem of residues from nut processing, the results suggest that the use of this practice might increase the nutborer population by concentrating odours which could attract the adults, or by disrupting the parasitoid or predator population. There is a need for testing other mulches such as plastics, other plant residues, sawdust and others, and to study alternative weed management systems, including the use of cover crops in the mid-rows.